Pluralism: the future of religion - Rose, Kenneth (Bloomsbury Academic, 2013)
Impasse in theology of religions -- The inclusivist counterrevolution -- The impossibility of an inclusivist revolution -- The syncretistic basis of the theory of apophatic pluralism -- Hinduism, the Upanishads, and apophatic pluralism -- The New Testament and apophatic pluralism -- The parable of the prisoners -- Apophatic pluralism and the study of religion.